Mechanistic insights into the anti-neuroinflammatory effects of cassia obtusifolia in Parkinson’s disease: a network pharmacology-based study - Lian, Xinfu; Bai, Yongjun; Xie, Rong; Du, Wang; Ma, Lingbo; Jiang, Yuqian (Frontiers in Aging Neuroscience, 2026)
BackgroundParkinson’s disease (PD) is a chronic neurodegenerative disorder that is closely associated with neuroinflammation, yet effective anti-inflammatory therapies remain limited. This study aimed to elucidate the potential mechanisms of Cassia obtusifolia in mitigating PD-associated neuroinflammatory responses.MethodsNetwork pharmacology was employed to identify bioactive compounds, candidate targets, and enriched pathways, followed by protein–protein interaction (PPI) analysis and molecular docking. Rhein, a representative compound, was further validated in LPS-induced BV2 microglial cells using CCK-8, NO detection, ELISA, and Western blot assays.ResultsA total of 114 candidate targets were identified, with enrichment highlighting NF-κB, MAPK, and NLRP3 inflammasome pathways. Molecular docking revealed strong binding affinity between rhein and NF-κB p65. In vitro, rhein significantly reduced the production of inflammatory mediators and suppressed p65 phosphorylation in BV2 cells.ConclusionCassia obtusifolia exerts multi-target anti-neuroinflammatory effects, supporting its potential as a therapeutic candidate for PD and providing a foundation for further translational studies.